Optimalisasi Produksi Alat Muat dan Alat Angkut dengan Metode Overall Equipment Effectiveness (OEE) Pada Pengangkutan Overburden Di Pit Barat PT. Artamulia Tata PratamaSite Tanjung Belit, Kabupaten Muaro Bungo, Provinsi Jambi - Sadam Husean; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2019)
Abstrack. Based on the production data of overburden stripping in western Pit PT. Artamulia Tatapratama in January-Februari 2018, overburden stripping production did not reach the target. This is due tothelow productivityof theexcavator.To find out the improvement potential of a production process and the effectiveness of using equipment, it is necessary to do an analysis using the Overall Equipment Effectiveness (OEE) method.. After knowing the root of the problem, multirple linear regression statistical analysis is used to determine the relationship and the maximum limits of the obstacles so that the production can be achieved. After doing the analysis and improvement with these methods, the production of the komatsu1250SP-8R excavator exceeded the planned target. However, the OEE value of eaoch excavator still <85% and has not reached the world-class OEE value> 85%, it can be concluded that the condition of the equipment is not good. It is better to do repairs to standby time and tool breakdown. Keywords: Production, Overall Equipment Effectiveness, multiple linear regression statistical analysis, Fishbone Method, komatsu 1250SP-8R excavator